High-dose immunosuppression to prevent death after paraquat self-poisoning–a randomised controlled trial - Indika Gawarammana (2018)
© 2017 Informa UK Limited, trading as Taylor & Francis Group. Context: Intentional self-poisoning with the herbicide paraquat has a very high case-fatality and is a major problem in rural Asia and Pacific. Objectives: We aimed to determine whether the addition of immunosuppression to supportive care offers benefit in resource poor Asian district hospitals. Materials and methods: We performed a randomised placebo-controlled trial comparing immunosuppression (intravenous cyclophosphamide up to 1 g/day for two days and methylprednisolone 1 g/day for three days, and then oral dexamethasone 8 mg three-times-a-day for 14 days) with saline and placebo tablets, in addition to standard care, in patients with acute paraquat self-poisoning admitted to six Sri Lankan hospitals between 1st March 2007 and 15th November 2010. The primary outcome was in-hospital mortality. Results: 299 patients were randomised to receive immunosuppression (147) or saline/placebo (152). There was no significant difference in in-hospital mortality rates between the groups (immunosuppression 78 [53%] vs. placebo 94 [62%] (Chi squared test 2.4, p =.12). There was no difference in mortality at three months between the immunosuppression (101/147 [69%]) and placebo groups (108/152 [71%]); (mortality reduction 2%, 95% CI: −8 to +12%). A Cox model did not support benefit from high-dose immunosuppression but suggested potential benefit from the subsequent two weeks of dexamethasone. Conclusions: We found no evidence that high dose immunosuppression improves survival in paraquat-poisoned patients. The continuing high mortality means further research on the use of dexamethasone and other potential treatments is urgently needed.